Crystallographic investigation, Hirshfeld surface analysis, NLO characterization and experimental spectral (UV and NMR) studies with DFT probe on(R)-9-(2-hydroxy propyl)adenine. Issue 4 (April 2021) - Sharmila Tagore, S.; Swaminathan, J.; Manikandan, D.; Gomathi, S.; Sabarinathan, N.; Ramalingam, M.; Sethuraman, V.
Abstract: In this study, (R)-9-(2-hydroxy propyl)adenine (HPA) is the molecule of interest for investigation. The XRD from single crystal of HPA has been used to extract its structural features. Since HPA crystallised in a non-centro symmetric space group P21 21 21, its NLO property was studied and it was found to exhibit very good SHG activity. To explore the intermolecular interactions the generated Hirshfeld surface has been investigated along with 2D-fingerprint plots. The experimental electronic and NMR spectra taken in the UV-visible and radio frequency regions respectively for HPA have been corroborated in correlation with theoretical predictions at Density Function Theory using 6-311++g (d, p) basis set. The experimental XRD geometrical parameters, chemical shifts of 13 C and 1 H and λmax values of HPA fit satisfactorily with the corresponding theoretically obtained numerical values as well as the stimulated spectrograms with the experimental ones. Further to explore the electronic structure, the MESP surface has been generated and investigated. The thermodynamic, kinetic and chemical reactivity features have been explored by means of frontier molecular orbitals of HPA. Abstract : Structural analysis; Hirshfeld surface analysis; NMR; UV; (R)-9-(2-hydroxy propyl)adenine.